Serological screening of SARS-CoV-2 infection in companion animals of Buenos Aires suburbs - Cardoso, Nancy Patricia; Rivero, Carla; Castillo, Mariangeles; Mansilla, Florencia Celeste; Pastorino, Florencia; Piccirilli, Guadalupe; Alonso, Laura; Martínez, Gustavo; Lullo, David Di; Bentancor, Leticia Veronica; Capozzo, Alejandra Victoria (Frontiers in Veterinary Science, 2023)
The Coronavirus Disease 2019 (COVID-19) is a zoonotic disease caused by the pandemic virus SARS-CoV-2. Domestic and wild animals are susceptible to infection and are potential reservoirs for virus variants. To date, there is no information about the exposure of companion animals in Buenos Aires Suburbs, the area with the largest population in Argentina where the highest number of COVID-19 human cases occurred during the first infection wave. Here we developed a multi-species indirect ELISA to measure antibodies reactive to the SARS-CoV-2 receptor-binding domain (RBD) from several vertebrates constituting the class Mammalia, making it a valuable tool for field serosurveillance. The ELISA cut-off value was estimated by sera from dogs, cats, cattle, and pigs sampled before 2019 (n=170), considering a 98% percentile and a grey zone to completely exclude any false positive result. Specificity was confirmed by measuring levels of neutralizing antibodies against canine coronavirus, the avidity of specific antibodies, and their capacity to impede the binding of a recombinant RBD protein to VERO cells in an In-Cell ELISA. Sera from 464 cats and dogs sampled in 2020 and 2021 (“pandemic” samples) were assessed using the RBD-ELISA. Information on COVID-19 disease in the household and the animals` lifestyles was collected. In Buenos Aires Suburbs cats were infected at a higher proportion than dogs, seroprevalence was 7.1% and 1.68%, respectively. Confirmed COVID-19 in the caregivers and outdoor lifestyle were statistically associated with seropositivity in cats. The risk of cats getting infected living indoors in COVID-19-negative households was null. The susceptibility of mammals to SARS-CoV-2, the possibility of transmission between animals themselves and humans, together with the free-roaming lifestyle typical of Buenos Aires suburban companion animals, urge pursuing responsible animal care and avoiding human interaction with animals during the disease course. The multi-species RBD-ELISA we developed can be used as a tool for serosurveillance of SARS-CoV-2 infection in mammalians (domestic and wild), guiding further targeted virological analyses to encounter susceptible species, interspecies transmission, and potential virus reservoirs in our region.